Peran Perguruan Tinggi dalam Meningkatkan Mutu Pendidikan dan Kesejahteraan Masyarakat Melalui Pengabdian Kepada Masyarakat - Hj. Elli Sulistyaningsih (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Universities have a significant contribution in improving the quality of human resources. Community Service is one of the pillars of the Tri Dharma of Higher Education, in addition to the dharma of education and teaching and the dharma of research. This is stated in Article 24 point 22 of Law No. 20 of 2003 concerning the National Education System. Community service by lecturers and students is the implementation of the practice of knowledge through counseling of performance skills that are conveyed to the community in the hope of providing solutions to real problems that occur in the community. It was further stated that the community service program was more directed at the utilization and application of research results and educational outcomes at universities, for the empowerment and welfare of the community.